2016
DOI: 10.1016/j.ajme.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid bone chondrosarcoma with cervical nodal metastasis: A case report

Abstract: Background: Hyoid bone chondrosarcoma is a very rare condition. This study presents a case report of low-grade chondrosarcoma of hyoid bone with cervical nodal metastasis. The study also presents preoperative radiological investigations, pathological examination and the follow-up of the case. Case presentation: A 42 years old female had a hard mass in the left submandibular region of the neck. The mass was 5.5 cm  7.5 cm and mobile with deglutition. Conclusions: Although the tumor was low grade, it showed cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This fact is associated with locoregional recurrence and a poor prognosis. In our systematic review, few cases reported cervical metastasis of CS [31][32][33] . In none of them PTC lymph node metastasis was found.…”
Section: -Discussionmentioning
confidence: 89%
“…This fact is associated with locoregional recurrence and a poor prognosis. In our systematic review, few cases reported cervical metastasis of CS [31][32][33] . In none of them PTC lymph node metastasis was found.…”
Section: -Discussionmentioning
confidence: 89%
“…Radiation therapy has been proposed to reduce tumour volume, as adjuvant therapy in some cases of residual tumours or in non-operable patients 6 , 11 , 22-24 . Cervical metastases of CS are rare, and neck dissection should be performed only if radiological or clinical evidence of disease is present 25-27 . In this review, some authors reported neck dissection when pathological lymph node was present, as well as thyroidectomy when needed 20 , 26-31 , 32-34 .…”
Section: Discussionmentioning
confidence: 99%
“…Metastases have been reported more frequently in the lung. [14,19] Our patient had bilateral cervical lymphadenopathy of inflammatory aspect and multiple bilateral pulmonary nodules suggestive of metastases.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%